Biosulfidogenesis Mediates Natural Attenuation in Acidic Mine Pit Lakes - Charlotte M. van der Graaf; Javier Sánchez-España; Iñaki Yusta; Andrey Ilin; Sudarshan A. Shetty; Nicole J. Bale; Laura Villanueva; Alfons J. M. Stams; Irene Sánchez-Andrea (Microorganisms, 2020)
Acidic pit lakes are abandoned open pit mines filled with acid mine drainage (AMD)—highly acidic, metalliferous waters that pose a severe threat to the environment and are rarely properly remediated. Here, we investigated two meromictic, oligotrophic acidic mine pit lakes in the Iberian Pyrite Belt (IPB), Filón Centro (Tharsis) (FC) and La Zarza (LZ). We observed a natural attenuation of acidity and toxic metal concentrations towards the lake bottom, which was more pronounced in FC. The detection of Cu and Zn sulfides in the monimolimnion of FC suggests precipitation of dissolved metals as metal sulfides, pointing to biogenic sulfide formation. This was supported by microbial diversity analysis via 16S rRNA gene amplicon sequencing of samples from the water column, which showed the presence of sulfidogenic microbial taxa in FC and LZ. In the monimolimnion of FC, sequences affiliated with the putative sulfate-reducing genus Desulfomonile were dominant (58%), whereas in the more acidic and metal-enriched LZ, elemental sulfur-reducing Acidianus and Thermoplasma spp., and disproportionating Desulfocapsa spp. were more abundant. Furthermore, the detection of reads classified as methanogens and Desulfosporosinus spp., although at low relative abundance, represents one of the lowest pH values (2.9 in LZ) at which these taxa have been reported, to our knowledge. Analysis of potential biomarker lipids provided evidence that high levels of phosphocholine lipids with mixed acyl/ether glycerol core structures were associated with Desulfomonile, while ceramide lipids were characteristic of Microbacter in these environments. We propose that FC and LZ function as natural bioremediation reactors where metal sulfide precipitation is mediated by biosulfidogenesis starting from elemental sulfur reduction and disproportionation at an early stage (LZ), followed by sulfate reduction at a later stage (FC).